On the genealogy of morals A polemic - Nietzsche, Friedrich (Lahore : Readings, 2023)
Written in 1887, On the Genealogy of Morals is a profound deconstruction of morality s evolution. This philosophical masterpiece scrutinizes the origins and implications of moral values, unravelling the complex interplay of power, guilt, and societal norms. Through incisive analysis and provocative aphorisms, Nietzsche challenges prevailing moral frameworks, exposing their historical underpinnings. On the Genealogy of Morals serves as a critical examination of human ethics, inviting readers to confront uncomfortable truths about societal conditioning and the dynamics of power. Nietzsche s penetrating insight and relentless intellectual rigour make this work a cornerstone for those navigating the intricate terrain of moral philosophy and cultural critique.
Keywords: Philosophical Critique; Friedrich Nietzsche; On the Genealogy of Morals